Concise Reporting of Benign Endometrial Biopsies is an Acceptable Alternative to Descriptive Reporting. (January 2022) - Kriplani, Divya; Olivar, Ana A.; Tchrakian, Nairi; Butcher, Deborah; Casey, Laura; Crook, Jonathan A.; Deo, Nandita; Dilley, James; Griffiths, Richard; Hogg, Matt; Jeyarajah, Arjun R.; Khan, Saima J.; et al.
Abstract : In the United Kingdom, endometrial biopsy reports traditionally consist of a morphologic description followed by a conclusion. Recently published consensus guidelines for reporting benign endometrial biopsies advocate the use of standardized terminology. In this project we aimed to assess the acceptability and benefits of this simplified "diagnosis only" format for reporting non-neoplastic endometrial biopsies. Two consultants reported consecutive endometrial biopsies using 1 of 3 possible formats: (i) diagnosis only, (ii) diagnosis plus an accompanying comment, and (iii) the traditional descriptive format. Service users were asked to provide feedback on this approach via an anonymized online survey. The reproducibility of this system was assessed on a set of 53 endometrial biopsies among consultants and senior histopathology trainees. Of 370 consecutive benign endometrial biopsies, 245 (66%) were reported as diagnosis only, 101 (27%) as diagnosis plus a brief comment, and 24 (7%) as diagnosis following a morphologic description. Of the 43 survey respondents (28 gynecologists, 11 pathologists, and 4 clinical nurse specialists), 40 (93%) preferred a diagnosis only, with 3 (7%) being against/uncertain about a diagnosis only report. Among 3 histopathology consultants and 4 senior trainees there was majority agreement on the reporting format in 53/53 (100%) and 52/53 (98%) biopsies. In summary, we found that reporting benign specimens within standardized, well-understood diagnostic categories is an acceptable alternative to traditional descriptive reporting, with the latter reserved for the minority of cases that do not fit into specific categories. This revised approach has the potential to improve reporting uniformity and reproducibility.